Perubahan Lingkungan Endapan Kuarter di Daerah Manado dan Sekitarnya, Sulawesi Utara - Santoso Santoso (Jurnal Geologi dan Sumberdaya Mineral, 2006)
Based on nine data from subsurfaces, the development of specific Quaternary sediments in the studied area is controlled by facies of floodbasin (Fcb), beach to transitions/tidal (Fpps), swamp (Fr), channel river (Fas), volcanic eruption (Feg), volacanic eruption which is influenced by water (Fegm), beach (Fp), and nearshore (Fldp). Corelation of successions of facies reflects the deposition of palaeoenvironment that is able to be divided into three periods, characterized by transgression and regression events. The development of the palaeoenvironment of deposition indicates that the position of shoreline changed from time to time. Perhaps, this is the result of changes in the depositional regime which is closely related to tectonic events.Â Keywords: facies, deposition of paleoenvironment, sea surface, tectonic